Strategi pengembangan umkm jamu di Kabupaten Sumenep - Ika Fatmawati; Ismawati Ismawati; Enza Resdiana (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Herbal medicine is one of the superior products of Sumenep Regency, including Ganding District. Herbal medicine producers in Ganding District are classified as Micro, Small, and Medium Enterprises (MSMEs). Herbal processing in Ganding District is done simply using traditional tools. The traditional production process in herbal medicine’s MSMEs usually only uses simple equipment and utilizes local workers. The aim of this research is to design a strategy for developing herbal medicine’s MSMEs in Ganding District, Sumenep Regency. This research method uses a qualitative descriptive approach. It was starting from identifying and assessing the conditions of business processes in herbal medicine’s MSMEs which are based on 4P and STP. The next step is determining the internal environmental factors of herbal medicine’s MSMEs by assessing the independent instrument based on CIMOSA. The external factors of herbal medicine’s MSMEs also need to be seen, which can be obtained from stakeholder identification. Then, proceed with developing a strategy based on the results of identifying internal and external environmental factors using the SWOT method. The analysis results show that the independence assessment carried out on herbal medicine producers in Ganding District did not reach a value of 62.5% and still had a value 2. This shows that herbal medicine’s MSMEs still do not meet the requirements for independence. The business strategy prepared covers all aspects of the herbal medicine busines’s MSMEs. This means that the strategy prepared includes strategic, operational, and supporting strategies. The strategy is based on weakness and opportunity using SWOT analysis and includes online marketing via social media, training from government agencies, and instruction on the use of technology.